Climate Change Impacts on Surface Water Resources of the Northern Region of Sri Lanka - Piratheeparajah, N. (BES, 2023)
This research assesses the influence of climate change on surface water resources situated in the northernprovince of Sri Lanka. The investigators analyzed hydro-climatic data using multiple techniques in order to determine the impact of climate change on crucial parameters related to the region’s surface water sources. Through Mann-Kendall trend analysis and Sen’s slope estimation, it was revealed that the rainfall and temperature within the study area have experienced an increase. Specifically, the yearly total rainfall has a growth rate of 24.6/decade, while the temperature has increased by 0.54°C/decade. The reduction of rainy days causes a noteworthy increase in runoff, while the increase in temperature leads to a higher level of evaporation, inducing water scarcity and drought in the study area due to the low water level or availability in the area. It is worth noting that the water supply inadequacy in the SWMS and FIMS is compounded further by high evaporation rates and temperatures. There is a strongly negative correlation between the decline of rainy days and the increased volume of runoff, with an R-value of -0.70. This is an indication that the reduction of rainy days increases the amount of runoff in the region due to the high intensity of rainfall over a short period. Meanwhile, there is a positive correlation between temperature and evaporation. The rate of evaporation has increased by 48mm/decade. Given these findings, it is suggested that increasing water holding capacity and constructing new reservoirs within the river basins of Aruvi Aru (lower stream), Paranki Aru (upper and lower stream), Pali Aru (lower stream), Per Aru (lower stream), and Mandaikallaru (upper and lower stream), as well as infiltration by maintaining porous surfaces with green coverage may help to reduce the impact of water scarcity and prevent frequent flooding.
Keywords: Climate change impacts; Surface water; Northern region